Assessment of Bacterial Load in Polyethylene Terephthalate (PET) Bottled Water Marketed in Kathmandu Valley, Nepal - Bikram Gautam; Gaumani Gyanwali; David Wayne Ussery (International Journal of Polymer Science)
In recent years, we are having mixed feelings regarding the use of polyethylene terephthalate (PET) bottles for storing water. The aim of this study is to determine any associations between bacterial load and the physical condition of the water bottle. For this study, bottled water was purchased, and parameters like pH, electrical conductivity (EC), total dissolved solids (TDS), heterotrophic plate count (HPC), total coliform count, and Pseudomonas spp. count were determined as per the American Public Health Association, 2005. The pH value of water samples tested ranged from 5.2 to 6.8. The majority of samples (96%) were found to contain pH values that were unacceptable as per the Department of Food Technology and Quality Control (DFTQC) guideline. Value of electrical conductivity (EC) ranged from 5 to 199 μS/cm. HPC revealed that, out of 100 samples, 48 (48%) samples were found to be acceptable as per the DFTQC guideline value (<25 cfu/mL). Among 100 samples, Pseudomonas spp. was found to be present in 23% of bottled water. Acidic pH and elevated concentrations of TDS and EC may lead to the survival of extremophiles present in HPC which may lead to degradation of PET. Extremophile bacteria that survive in bottled water for a long time rely on several survival mechanisms including evolutionary development (evo-devo) and solely survive on complex polymers like PET.